The mind-body problem in Descartes and contemporary philosophy (Diametros, 2009)
The article highlights the most important elements of Descartes’ philosophy that have contributed to the development of the debate about the mind-body problem. The basis of Descartes’ ontological dualism is presented from the point of view of contemporary philosophical discussions; in the final part of the analysis a critical evaluation is carried out. The possibility and necessity of investigating the problematic in question also makes reference to the future. The methodic procedure used in the article is applied to both the a priori and a posteriori domains.